Studi Literatur: Peranan Higher Order Thinking Skills Dalam Proses Pembelajaran - Nofamataro Zebua (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This article discussed the important role of Higher Order Thinking Skills (HOTS) in the learning process. Critical thinking skills, creative, and problem-solving skills in the 21st century is essential to prepare competent young generation. Despite the rapid development of technology, Indonesia's PISA score is still very low. Improving the curriculum by prioritizing the development of HOTS-based skills can be a solution to deal with this phenomenon. The method which used in conducting this article is the literature study method. This method is used in collecting data, analyzing, and synthesizing the findings by specifying the topic of the role of HOTS in the learning process. The conclusion is that the integration of HOTS in learning is the key to preparing students who are able to think critically, creatively and solve problems that encountered in their environment.